The kinematic analysis of the lateral airflip motion on the balance beam apparatus of the 2008 world champions (Journal of the College of Basic Education, 2022)
Through the researcher's experience in the field of gymnastics as a player, coach and international referee, she noticed thatThe continuous change in the skills and movements of artistic gymnastics is carried out by increasing the difficulty and diversification in variousThe devices are from the movements of the pilot or the flips and rotations, so the researcher found that the skill of the lateral pneumatic flipsOf the difficult and underutilized skills, regardless of whether they are included in the compulsory seriesIn the balance beam device, as it is distinguished from the front and rear antennas in terms of